A porous nitrogen and phosphorous dual doped graphene blocking layer for high performance Li–S batteries1. Issue 32 (28th August 2015) - Gu, Xingxing; Tong, Chuan-jia; Lai, Chao; Qiu, Jingxia; Huang, Xiaoxiao; Yang, Wenlong; Wen, Bo; Liu, Li-min; Hou, Yanglong; Zhang, Shanqing
<x xml:space="preserve">Abstract</x> A porous N and P dual doped graphene interlayer was fabricated for improved conductivity and polysulfide capture in Li–S batteries, supported by first-principles DFT calculations.